Epidemiology of exertional heat illnesses in organised sports: A systematic review - Gamage, P. J.; Fortington, L. V.; Finch, C. F. (Journal of Science and Medicine in Sport, 2020)
Objective: This systematic review summarises reports of the incidence of exertional heat illnesses (EHI) in organised sports, to examine any trends in the EHI incidence over time, and to describe EHI incidence based on sporting activity, geographic location, and type of EHI. Method: Three electronic databases (CINAHL, PubMed, SportDiscuss) were searched from inception to January 2019. Original data in all epidemiological studies (any design except case-studies and case-series) that reported EHI incidence data in organised sports, across all age categories, and published in an English language peer-reviewed journal were included. Results: The primary search yielded 3556 results of which 62 studies were included in the final analysis, with 71% being from the USA. Reported EHI incidence rates ranged from 0.01 (cheerleading) to 4.19 (American football) per 1000 athletic-exposures (AEs), and 0.01 (mini-marathon) to 54.54 (desert ultra-marathon) per 100 participants. Endurance type events (running, cycling, adventure races) reported the highest EHI incidence rates per 100 participants. There was a considerable increase in EHI fatalities reported in the literature over the last three decades in American football and an increased reporting of EHI incidence in endurance type events during the last 5-years. Conclusion: Use of different terminology and injury definitions in most studies have resulted in an inconsistency in reporting EHI incidence data, and also likely underreporting of less-severe forms of EHI conditions. Longitudinal studies focused on different sports and conducted in more countries (outside the USA), are needed for better understanding the global impact of EHI and the impact of prevention measures.